Absolute configurations of new cembrane-type diterpenoids from the Hainan soft coral Sarcophyton crassocaule. Issue 25 (18th June 2020) - Ye, Fei; Gu, Yu-Cheng; Guo, Yue-Wei; Li, Xu-Wen
Graphical abstract: Highlights: New cembranoids were isolated and identified from the Hainan soft coral Sarcophyton crassocaule . A pair of enantiomers were purified by chiral HPLC. The absolute configurations were determined by TDDFT-ECD calculation, modified Mosher's method, and/or Snatzke's method. Abstract: The determination of the stereochemistry of cembrane type diterpenoids is always a challenging task due to the flexibility of the 14-membered macrocycle. In this paper, three new cembranoids, ximaocembrols A–C (1 –3 ), were isolated from the Hainan soft coral Sarcophyton crassocaule, and ximaocembrol C was further separated by chiral HPLC to its corresponding enantiomers (±)-3, respectively. The absolute configurations of these new compounds were successfully elucidated by using a series of reliable approaches, including extensive spectroscopic analysis, TDDFT-ECD calculation, modified Mosher's method, and Snatzke's method.